Legal Review of Hospital Responsibility for Medical Actions Carried Out By Doctors - Arief Fakrulloh, Zudan; Lubna, Lubna (CV. Publikasi Indonesia, 2023)
Every person has the right and legal right to obtain health services, and the public is free to utilize government and/or regional government health resources. The organization of hospital administration services, medical services, supporting services, and nursing services, both inpatient and outpatient must be provided at a minimum by the hospital, by regional hospital service standards. This type of research is normative juridical research, that is, it is studied using a statutory approach, meaning that a problem will be seen from its legal aspect by examining statutory regulations. Based on Number 44 of 2009 concerning Hospitals, hospitals are legally responsible for all losses incurred due to negligence committed by health workers at the hospital. The hospital's legal responsibility in providing health services to patients can be seen in professional ethics, administrative law, civil law, and criminal law